Reclassification of 11 Members of the Family Rhodobacteraceae at Genus and Species Levels and Proposal of Pseudogemmobacter hezensis sp. nov. - Ma, Tengfei; Xue, Han; Piao, Chungen; Liu, Chengyi; Yang, Mei; Bian, Danran; Li, Yong (Frontiers in Microbiology, 2022)
A novel Gram-stain-negative, aerobic, motile bacterial strain, D13-10-4-6T, was isolated from the bark sample of Populus×euramericana. The strain could grow at 15–35 ℃, at pH 6–10 and in 0–4% (w/v) NaCl, and the strain tested positive for oxidase and catalase activities. The main polar lipid were phosphatidylmonomethylethanolamine, diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine. The main respiratory quinones was Q-10, and predominant fatty acids was C18:1 ω7c. The phylogenetic analyses showed that the strain belonged to genus Pseudogemmobacter of family Rhodobacteraceae. Family Rhodobacteraceae is an ecologically diverse group that includes bacteria from aquatic to terrestrial ecosystems. As a consequence of that, the classification of family Rhodobacteraceae is difficult, not least when the early taxonomy work relied heavily on 16S rRNA gene analysis. Recently, the taxonomic status of many members of the family have been revised based on the genome analysis, however, there are still some classification conflicts due to the lack of genome sequences and parallel publication time. In present study, phylogenetic trees based on 16S rRNA gene, gyrB gene and 120 concatenated proteins, average amino acid identity and percentage of conserved proteins have been used for the analysis for strain D13-10-4-6T and other members of 15 genera within the family, to further clarify their taxonomic relationships. On the data of phylogeny, AAI and POCP, the following taxonomic proposals are made: (1) reclassification of Rhodobacter tardus as the type species of a novel genus, Stagnihabitans gen. nov., as Stagnihabitans tardus comb. nov.; (2) reclassification of Tabrizicola alkalilacus, Tabrizicola sediminis, Tabrizicola algicola into a novel genus, Pseudotabrizicola gen. nov., as Pseudotabrizicola alkalilacus comb. nov., Pseudotabrizicola sediminis comb. nov., Pseudotabrizicola algicola comb. nov.; (3) reclassification of Rhodobacter sediminicola into genus Cereibacter as Cereibacter sediminicola comb. nov.; (4) reclassification of Rhodobacter flagellatus, Rhodobacter thermarum and Xinfangfangia soli into genus Tabrizicola as Tabrizicola flagellatus comb. nov, Tabrizicola thermarum comb. nov and Tabrizicola soli comb. nov.; (5) reclassification of Xinfangfangia humi into genus Pseudogemmobacter as Pseudogemmobacter humicola comb. nov.; (6) classify strain D13-10-4-6T as a novel species of genus Pseudogemmobacter, for which the name Pseudogemmobacter hezensis sp. nov. is proposed, the type strain is D13-10-4-6T (=CFCC 12033T =KCTC 82215T).